Boosting Writing Skill in Junior High School Students Through Simultaneous Roundtable and Picture-Based Techniques - Aryanti, Ni Made Febyana Sri; Krismayani, Ni Wayan; Kumara, Dewa Gede Agung Gana (PROJECT (Professional Journal of English Education), 2025)
Writing in English requires a good mastery of structure and composition. Therefore, students must master the essential elements of writing. This classroom action research aimed to improve seventh-grade students' writing skills at SMPN 3 Ubud using the Simultaneous Roundtable technique combined with pictures. A post-test is given at the end of each cycle to collect the necessary data. Initial observations on seventh-grade students showed that their writing skills needed improvement by combining Simultaneous Roundtables with pictures. The post-tests I and II results significantly increased subject and category writing abilities. The pre-test results were 39.44, post-test I  were 60.65, and post-test II were 71.34. The researcher gave a questionnaire at the end of the session, and the results showed an improvement in students' writing skills. The percentage of the strongly agreed questionnaire shows that 53 % of subjects strongly agree. 43 % of subjects agreed, 4 % of subjects were unsure, 0% of subjects disagreed, and 0 % strongly disagreed. In conclusion, this classroom action research proves that the writing skills of seventh graders can be improved through simultaneous roundtables with pictures.